Molecular characterization of lactic acid bacteria producing edible biofilm isolated from kimchi - FADILLA SAPALINA; Endah Retnaningrum (Society for Indonesian Biodiversity, 2020)
Biofilm is a community of microorganisms that interrelated and covered by an extracellular polymer matrix. This biofilm can be produced by Lactic acid bacteria (LAB) which was edible for human and animal.  Therefore, it possible to be applied in the food and health industry. One source of LAB is kimchi, as fermented food from Korea and it has good benefits for health. This research aimed to obtain LAB from kimchi that can produce edible biofilms and to identify LAB producing edible biofilms based on the 16S rRNA gene. Isolation of lactic acid bacteria from kimchi cultured in MRS agar medium containing 1% CaCO3, biofilm production test with biofilm assay method and zeolite as a substrate to adherent cells. For amplification of 16S rRNA gene used primer 27F and 1492R. The isolate of KA2, KA5, KB1, and KC4 isolated from kimchi and could produce biofilms with the highest biofilm formation at 48 hours incubation time. Based on molecular identification with 16S rRNA gene sequencing, the four isolates identified as Lactobacillus brevis species.